A comprehensive review on Brigatinib - A wonder drug for targeted cancer therapy in non-small cell lung cancer - Silky Bedi; Shah A. Khan; Majed M. AbuKhader; Perwez Alam; Nasir A. Siddiqui; Asif Husain (Elsevier, 2018)
The mortality rate in patients suffering from non-small cell lung cancer (NSCLC) is quite high. This type of cancer mainly occurs due to rearrangements in the anaplastic lymphoma kinase (ALK) gene which leads to form an oncogene of fused gene NPM-ALK. Brigatinib is recently approved by FDA in April 2017 as a potent tyrosine kinase inhibitor (TKI) for the NSCLC therapy. In the present scenario, it is no less than a wonder drug because it is indicated for the treatment of advanced stages of metastatic ALK positive NSCLC, a fatal disease to overcome the resistance of various other ALK inhibitors such as crizotinib, ceritinib and alectinib. In addition to ALK, it is also active against multiple types of kinases such as ROS1, Insulin like growth factor-1Receptor and EGFR. It can be synthesized by using N-[2-methoxy-4-[4-(dimethylamino) piperidin-1-yl] aniline] guanidine and 2,4,5-trichloropyrimidine respectively in two different ways. Its structure consists of mainly dimethylphosphine oxide group which is responsible for its pharmacological activity. It is active against various cell lines such as HCC78, H2228, H23, H358, H838, U937, HepG2 and Karpas- 299. Results of ALTA (ALK in Lung Cancer Trial of AP26113) phase ½ trial shows that 90 mg of brigatinib for 7 days and then 180 mg for next days is effective in the treatment of NSCLC. Brigatinib has been shown to have favorable risk benefit profile and is a safer drug than the available cytotoxic chemotherapeutic agents. In comparison to other FDA approved drugs for the same condition, it causes fewer minor adverse reactions which can be easily managed either by changing the dose or by providing good supportive care. This article is intended to provide readers with an overview of chemistry, pharmacokinetic, pharmacodynamic and safety profile of brigatinib, which addresses an unmet medical need. Keywords: ALK inhibitors, Brigatinib, Lung cancer, Kinase, Lymphoma